Experimental analysis on refrigeration system using CNT, gold & HAUCL4 nano fluids. (2020) - Mohan, K.; Sundararaj, S.; Gopi Kannan, K.; Kannan, A.
Abstract: In this paper the experimental analysis on exergy performance of vapour compression refrigeration system (VCRS) with nanoparticles was carried out. CNT, gold and HAuCl4 nanoparticles were suspended with a conventional lubricant, polyalkylene glycol. Volume percentage of nanoparticles used with polyalkylene glycol were 0.1% gold, 0.2% gold, 0.1% HAuCl4, 0.2% HAuCl4, 0.1% gold with 0.005% CNT and 0.2% gold with 0.005% CNT. Tests were conducted to determine the cooling time required for evaporator water temperature to lower from 25 °C to 4 °C, coefficient of performance (COP) and exergy losses in the VCRS components. The experimental result shows that for 0.2% gold with 0.005% CNT, a lowest cooling time of about 1600 s recorded and for 0.1% gold with 0.005% CNT, a COP increase of 31.7% was achieved. Also the results indicates that for system compared with conventional refrigerant (R134a) with lubricant, 0.1% gold with 0.005% CNT nanoparticle suspension yields reduced exergy loss of 8%. Also 0.1% gold with 0.005% CNT nanoparticle suspension requires less power input to compressor as compared to conventional system.